Inwestycje infrastrukturalne jako źródło konfliktu przestrzennego na przykładzie projektu PHARE "Przebudowa drogi wojewódzkiej nr 713 Łódź-Tomaszów Mazowiecki" - Nowak, Magdalena (Infrastructural Investment as a Source of a Spatial Conflict- on the Example of Phare Project "Reconstruction of Voivodship Road No 713 between Łódź and Tomaszów Mazowiecki", 2006)
When managing the space, there is often a need of compromise between contradictory interests which can become a source of a spatial conflict. Those conflicts can arise on the basis of infastructural investment which is perceived negatively by the local community. Nevertheless there can be a situation when the investment itself is estimated positively but the process of its implementation becomes highly inconvenient for the local community. Realization of a PHARE project "Reconstruction of voivodship road No 713 between Łódź and Tomaszów Mazowiecki" is an example of such situation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 715-724